The formation of micro-blisters on Al–Mg alloy surfaces during hot rolling. (July 2015) - Gali, O.A.; Shafiei, M.; Hunter, J.A.; Zhao, Q.; Riahi, A.R.
Abstract: Micro-blisters occurring on the surfaces of Al–Mg alloys after the first hot rolling pass were studied. The micro-blisters had a nanocrystyalline structure and comprised of an outer MgO shell and an inner Al/Al2 O3 lining. It is proposed that the micro-blisters are linked to the presence of carbide particles protruding from the work roll surface and the evolution of hydrogen from the reaction of water vapor, permeated through the porous oxide-rich surface layer, with the bulk aluminum. Highlights: Blisters occurred on the surfaces of Al–Mg alloys after the first hot rolling pass. Blisters were linked to low lubrication and carbides protruding from the work roll. Blisters had a nanocrystalline shell structure comprised of layers of MgO/Al/Al2 O3 . The mechanism of blister formation was proposed. The mechanism is linked to hydrogen evolution and oxide layer adhesion to carbides.